Inhibitory deficits and symptoms of attention‐deficit hyperactivity disorder: How are they related to effortful control?. (20th September 2022) - Kostyrka‐Allchorne, Katarzyna; Wass, Sam V.; Yusuf, Hodo; Rao, Vidya; Bertini, Chloé; Sonuga‐Barke, Edmund J. S.
Abstract: Separate studies with clinical and community‐based samples have identified an association between symptoms of attention‐deficit hyperactivity disorder (ADHD) and inhibitory control deficits and ADHD and weak effortful control. We tested whether differences in effortful control explained the associations between ADHD symptoms and inhibitory control deficits, controlling for conduct problems. In a community sample, parents rated ADHD symptoms, conduct problems, effortful control, surgency and negative affect in 77 4‐7‐year‐olds (47 girls), who performed an inhibitory control task. ADHD symptoms, deficient inhibitory control and low effortful control were correlated. Controlling for conduct problems, path analysis showed the ADHD symptoms – inhibitory control link was mediated statistically by effortful control. This focuses attention on cognitive‐energetic factors associated with ADHD‐related executive deficits.